2014
DOI: 10.1007/s00417-014-2867-0
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal bevacizumab monotherapy for type-1 prethreshold, threshold, and aggressive posterior retinopathy of prematurity — 27 month follow-up results from Turkey

Abstract: IVB injection as monotherapy seems to be a very effective treatment modality for ROP. Based on timely intervention, IVB as a single treatment modality can salvage almost all ROP cases before stage 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 29 publications
2
36
0
3
Order By: Relevance
“…These changes in retinal vasculature were also different from the pattern of APROP regression either naturally or following laser. We compared the observed vascular events with reports on similar changes of any kind after IVB 15,[25][26][27][28][29] (Table 3) at different doses reported so far in the literature. The saw-toothed shunts observed in all the seven eyes in our series had a striking resemblance to the recent description of 'tungsten filament sign' by Yetik et al 29 and needs special mention.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These changes in retinal vasculature were also different from the pattern of APROP regression either naturally or following laser. We compared the observed vascular events with reports on similar changes of any kind after IVB 15,[25][26][27][28][29] (Table 3) at different doses reported so far in the literature. The saw-toothed shunts observed in all the seven eyes in our series had a striking resemblance to the recent description of 'tungsten filament sign' by Yetik et al 29 and needs special mention.…”
Section: Discussionmentioning
confidence: 92%
“…We compared the observed vascular events with reports on similar changes of any kind after IVB 15,[25][26][27][28][29] (Table 3) at different doses reported so far in the literature. The saw-toothed shunts observed in all the seven eyes in our series had a striking resemblance to the recent description of 'tungsten filament sign' by Yetik et al 29 and needs special mention. Although we agree with them that these could be pathognomonic sign of IVB injection in preterm babies, the fact that there were severe preretinal hemorrhage overlying it in one eye and progression to abnormal circumferential vessels in the other 3 eyes makes us to believe that they may not always be the marker of regression and should be followed up with care and caution.…”
Section: Discussionmentioning
confidence: 92%
“…Intravitreal anti-VEGF therapy has been increasingly used in severe ROP cases; hence, whether or not the systemic leakage of anti-VEGF can cause any short-or longterm adverse effects on the tissues or organs has always been an issue (10)(11)(12)(13)(14). The effects of this therapy on other tissues, including the lungs, were not investigated thoroughly in the present study, although we have previously reported a better systemic clinical course of BPD in preterm babies after the injection of IVB (10).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in recent years a new treatment modality involving the intravitreal injection of anti-VEGF (vascular endothelial growth factor) agents (intravitreal bevacizumab (IVB)) has been used in the treatment of ROP with high success rates of up to 100% in even the most aggressive forms of the disease (10)(11)(12)(13)(14). However, anti-VEGF agents can gain access to the systemic circulation following an intravitreal injection (15)(16)(17)(18)(19), and the systemic adverse effects of intravitreal anti-VEGF agents have always been a concern.…”
Section: Introductionmentioning
confidence: 99%
“…63,64,65,66 PROGNÓSTICO APÓS O TRATAMENTO DA ROP A ROP habitualmente regride na maioria dos pacientes que desenvolvem apenas os estadiamentos 1 ou 2, pois a vascularização da retina periférica pode ir se completando nas semanas seguintes ao nascimento prematuro, deixando poucas alterações anatômicas e funcionais residuais que não necessitam de nenhum tratamento específico. Esses pacientes precisam apenas de acompanhamento evolutivo, durante os primeiros anos de sua vida, para a prevenção de ambliopia e do estrabismo e para a correção de ametropias, cujas incidências parecem ser maiores em RNP, quando comparadas com nascidos não prematuros.…”
Section: 5152unclassified